The Effect of Refugia Crops on the Abundance of Insect Pests and Natural Enemies in Fruits Plantations - Putri, Vadila Mulia; Windriyanti , Wiwin; Rahmadhini, Noni (Universitas Muhammadiyah Prof. Dr. Hamka, 2025)
Background: Refugia plants can provide SNAP (Shelter, Nectar, Alternative food, and Pollen) for insects. Commonly used refugia plants are marigolds (Tagetes erecta), zinnia (Zinnia elegans), and king's salad (Cosmos caudatus). Planting refugia plants is one way to manipulate the habitat of natural enemies so natural enemy populations increase, and pest populations can be controlled. Abiotic factors like temperature, humidity, pH, and rainfall affect insect populations. Methods: This research was conducted in March–May 2023. The refugia plants used were king's salad and zinnia flowers with a cropping pattern on the edges of the plots and an insect bank system. Sampling data was collected from both fields twice weekly using observation, sticky yellow traps, sweep nets, and light traps. Results: Insect pests and natural enemies from both fields were identified, namely four orders, 11 families, and 13 morphospecies, with 503 insects in the plantations with refugia and 434 without refugia. Conclusions: Species diversity values were 2.12 and 2.08 in plantations with and without refugia, indicating moderate diversity. The Bray-Curtis index for planting insect groups with and without refugia was 0.903, indicating the constituents' composition was the same. Based on the linear regression test results, the temperature and humidity factors affect insect pests' Abundance and natural enemies' Abundance.